Cobalt-catalyzed aminoalkylative carbonylation of alkenes toward direct synthesis of γ-amino acid derivatives and peptides - Le-Cheng Wang; Yang Yuan; Youcan Zhang; Xiao-Feng Wu (Nature Communications, 2023)
Abstract γ-Amino acids and peptides analogues are common constituents of building blocks for numerous biologically active molecules, pharmaceuticals, and natural products. In particular, γ-amino acids are providing with better metabolic stability than α-amino acids. Herein we report a multicomponent carbonylation technology that combines readily available amides, alkenes, and the feedstock gas carbon monoxide to build architecturally complex and functionally diverse γ-amino acid derivatives in a single step by the implementation of radical relay catalysis. This transformation can also be used as a late-stage functionalization strategy to deliver complex, advanced γ-amino acid products for pharmaceutical and other areas.